INSULIN SEBAGAI PENGATUR KADAR GULA DARAH - Uswatun Hasanah (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT Insulin (in Latin insula, meaning "island", since it is produced in Langerhans islands in pancreas) is as polipeptide hormone controlling the carbohidrate metabolism.  Beside   the main effector in carbohidrate homeostatic, this hormone also takes a part in fat metabolism (trigliceride) and protein.  This hormone has anabolic property.  This hormone also influences other body vessels.  Insulin causes the cell (biology) on the muscles and adipose absorbing glucose from blood circulation through  glucose transporter (GLUT1 dan GLUT4)   and keep it as glicogen in liver and muscle as energy source. Low insulin degree will reduce glucose absorption and the body will start using fat as energy resource.  There are two deformities as the effect of insulin disturbance.  First, deformity on the pancreas leading the insulin can not be produced.  This condition is called as diabetes type 1.  Second, pancreas may produce insulin with inadequate number. Or, it may be with normal amount, but body cells do not use them (resistance).  This condition is called as diabetes type 2.  Insulin can be used for the treatment of some types of diabetes disease.  The patient with diabetes mellitus type 1 depends on the exogen insulin (injected into skin/subcutant). Those patients of diabetes mellitus type 2 have low insulin reproduction or insulin immune and sometimes it requires insulin arrangement once other treatments is not sufficient to control blood glucose degree. Kata Kunci : Insulin, kadar gula darah.